Green supply chain in Vietnam’s agricultural export activities - Le, Nguyen Vi; Huyen, Pham Thi (International Journal of Innovative Research and Scientific Studies, 2025)
The Vietnamese agricultural sector has grown rapidly in foreign markets, becoming a vital part of the global agricultural value chain. Poor product value, weak supply chain integration, and limited sustainable practices persist despite the rise in export turnover. This article evaluates green supply chain management (GSCM) in Vietnam’s agriculture export sector and proposes ways to improve it. A mixed-methods study included quantitative survey data along with qualitative expert interviews. 191 agricultural exporters, government entities, and logistical suppliers provided data. Structured surveys to analyze GSCM implementation aspects and semi-structured interviews for qualitative insights are essential. The study’s hypotheses were tested using reliability, exploratory factor analysis (EFA), and regression modeling. Policy direction is the biggest element in GSCM success, followed by managerial awareness, resource availability, and stakeholder understanding. Significant data show that Green Supply Chain Management (GSCM) improves environmental and economic results while meeting international standards. Case studies of successful enterprises show that Agriculture 4.0 and circular economy strategies improve export efficiency and import compliance. However, limited finances, technical infrastructure, and managerial skills restrict usage. The paper suggests regulatory reforms, specialized management units, and digital technology investment to overcome these challenges. This report concludes that GSCM is essential to Vietnam’s agricultural competitiveness. Increasing financial incentives, promoting international cooperation, and utilizing blockchain technology for traceability are recommended. The study’s weaknesses include a focus on export sectors and a lack of longitudinal data. Future research should examine cross-sectoral usage and the long-term consequences of GSCM.